Growth and Yield Response of Red Onion (Allium ascalonicum L.) Grown in Different Potting - H. Seran, N. Suthamathy; Thayamini (Journal of Phytology, 2011)
An experiment was conducted to evaluate the growth and yield response of red onion (Allium ascalonicum L.) grown in different potting media. Potting materials were sandy soil, cattle manure, coir dust and paddy husk ash. The media such as medium 1 used as control (sandy soil: cattle manure at ratio (v/v) of 6:2), medium 2 (sandy soil: cattle manure: coir dust atÃ‚Â ratio of 6:2:1), medium 3 (sandy soil: cattle manure: paddy husk ash at ratio of 6:2:1) and medium 4 (sandy soil: cattle manure: coir dust : paddy husk ash at ratio of 12:4:1:1) were prepared two weeks before planting. Bulbs were planted in each pot and other agronomic practices were done as recommended by Department of Agriculture, Sri Lanka. Plant height and number of leaves per plant were recorded at two week intervals. At the time of harvesting, fresh and air dry weights of plant, number of bulbs per plant, bulb diameter, bulb length, weight of bulbs per plant and nutrient (P and K) contents were measured and data were analyzed. The results indicated that potting materials have significant (p<0.01) effect on the growth, yield and nutrient contents of red onion grown in different potting media. Maximum number of leaves per plant, maximum bulb diameter, high number of bulbs per plant, high weight (50.15 g) of bulbs per plant and also high P (74 g) and K (1080 g) contents of 100 g bulbs harvested were recorded in medium 3 among tested media. It was also noted that the weight of bulbs per plant increased more than two fold in medium 3 over control (medium 1). Usage of paddy husk ash as a potting material in medium preparation would improve the growth and yield performances of red onion grown in pot culture technique. Key words: Cattle manure, Coir dust, Nutrient contents, Onion, Paddy husk ash, Yield <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">N. Suthamathy and Thayamini. H Seran. Growth and Yield Response of Red Onion (Allium ascalonicum L.) Grown in Different Potting. J Phytol 3/1 (2011) 50-58